Molecular Characterization of Enterococcus Isolates From Different Sources in Estonia Reveals Potential Transmission of Resistance Genes Among Different Reservoirs - Aun, Erki; Kisand, Veljo; Laht, Mailis; Telling, Kaidi; Kalmus, Piret; Väli, Ülo; Brauer, Age; Remm, Maido; Tenson, Tanel (Frontiers in Microbiology, 2021)
In this study, we aimed to characterize the population structure, drug resistance mechanisms and virulence genes of Enterococcus isolates in Estonia. 61 Enterococcus faecalis and 34 Enterococcus faecium isolates were collected between 2012 and 2014 across the country from various sites and sources, including farm animals and poultry (n=53), humans (n=12), environment (n=24) and wild birds (n=44). Clonal relationships of the strains were determined by whole genome sequencing and analyzed by multi-locus sequence typing. We determined the presence of acquired antimicrobial resistance genes and 23S rRNA mutations, virulence genes and also the plasmid or chromosomal origin of the genes using dedicated DNA-sequence analysis tools available and/or homology search against an ad-hoc compiled databases of relevant sequences. Two E. faecalis isolates from human with vanB genes were highly resistant to vancomycin. Closely related E. faecalis strains were isolated from different host species. This indicates interspecies spread of strains and potential transfer of antibiotic resistance. Genomic context analysis of the resistance genes indicated frequent association with plasmids and mobile genetic elements. Resistance genes are often present in the identical genetic context in strains with diverse origins suggesting the occurrence of transfer events.